Acute toxicity of heavy metals to the Malaysian giant prawn, Macrobrachium rosenbergii (de man) - M. Shazili, Noor A.; Mohd Ali, Azizan
The acute tocicity of the heavy metals,cadmium,copper,zinc and lead were determined for juvenile Macrobrachium rosenbergii. Toxicity tests were carried out in a static-with-renewal system over 12 days. The median lethal time (LT50)decreased with increasing concentration of copper and zinc. Slope function values for cadmium and lead showed a variable trend with concentration indicating greater variability in mortality response to these metals compared to copper and zinc. The median lethal concentrations at 48 hours (48hr LC50) were 0.11mg Cd/L,0.0036mg Cu/L and 0.16mg Zn/L and 0.12mg Pb/L,while 96hr LC50 values were 0.04mg Cd/L, <0.01mg Cu/L and <0.1mg Pb/L. The gills are possibly the primary target organ of cadmium and zinc action. The toxicity data were compared with lethal concentrations found for other crustaceans. Safety levels for the metals investigated are discussed in relation to existing water quality standards. Cadmium,copper,lead and zinc are heavy metals released from natural sources a well as human activity. They may accumulate in aquatic environments through runoff and in municipal and industrial areas through sewage discharge (Polprasert, 1982;Badri,1987). Many metals such as copper and zinc, are essential at low levels tothe survival of aquatic organism,but can be toxic when present in excess (Muramoto,1981;Zaba and Harris.1978;Westernhagen et al.,1979);Crespo,1984). However the effects of common metal pollutants on commercially important species in Malaysia are as yet little studied. The purpose of this investigation is to determine the acute tixicity of cadmium,copper,zinc and lead to the Malaysian giant prawn, Macrobrachium Rosenbergii. From these experiments the safe concentrations of these metals were estimated using application or safety-factors.